Early postoperative remodelling following repair of tetralogy of Fallot utilising unsedated cardiac magnetic resonance: a pilot study. (15th February 2018) - DiLorenzo, Michael P.; Goldmuntz, Elizabeth; Nicolson, Susan C.; Fogel, Mark A.; Mercer-Rosa, Laura
Abstract: Introduction: The right ventricular adaptations early after surgery in infants with tetralogy of Fallot are important to understand the changes that occur later on in life; this physiology has not been fully delineated. We sought to assess early postoperative right ventricular remodelling in patients with tetralogy of Fallot by cardiac MRI. Materials and method: Subjects with tetralogy of Fallot under 1 year of age were recruited following complete surgical repair for tetralogy of Fallot. Protocol-based cardiac MRI to assess anatomy, function, and flows was performed before hospital discharge using the feed and sleep technique, an unsedated imaging technique. Results: MRI was completed in 16 subjects at a median age of 77 days (interquartile range 114). There was normal ventricular ejection fraction and indexed right ventricular end-diastolic volume (48±13 cc/m 2 ), but elevated right ventricular mass (z score 6.2±2.4). Subjects requiring a transannular patch or right ventricle to pulmonary artery conduit had moderate pulmonary insufficiency (regurgitant fraction 27±16%). Discussion: Early right ventricular remodelling after surgical repair for tetralogy of Fallot is characterised by significant pulmonary regurgitation, right ventricular hypertrophy, and lack of dilation. Performing cardiac MRI using the feed and sleep technique is feasible in infants younger than 5 months. These results might open new avenues to study longitudinal right ventricular changes in tetralogy of Fallot and to further explore the utility of unsedated MRI in patients with other types of CHDs.